Knowledge, attitudes, and practices of rational drug prescribing in Nigerian Navy - Ahmadu Shehu Mohammed; Babatunde Enitan Ogunnowo; Odekunle Bola Odegbemi (Discover Public Health)
Abstract Background Rational Drug Prescribing (RDP) optimizes therapeutic outcomes by aligning medication use with patient needs while minimizing risks and costs. Irrational prescribing, however, remains prevalent globally and in resource-constrained settings like Nigeria. This study focuses on physicians in Nigerian Navy hospitals, which serve both military and civilian populations, providing critical insights into their knowledge, attitudes, and practices (KAP) of RDP. Methods A descriptive cross-sectional study was conducted in three Nigerian Navy hospitals in Lagos State. Sixty-one physicians were surveyed using structured questionnaires, and 600 prescriptions were analyzed using WHO drug use indicators. Data collected included the average number of drugs per encounter, generic prescribing rates, antibiotic and injection use, and adherence to the Nigerian Essential Drug List (EDL). “Good knowledge” was defined as a score ≥ 75% on the knowledge questionnaire, and attitudes were assessed via a Likert scale. Results Among participants, 85.2% demonstrated good knowledge of RDP, yet only 16.4% had formal training. Positive attitudes were reported by 67.2%, but consistent adherence to rational prescribing practices was observed in only 29.5%. Prescription analysis revealed an average of 3.78 drugs per encounter, exceeding the WHO recommendation of ≤ 2 drugs per encounter. Antibiotics and injections were prescribed in 46.3% and 24.5% of cases, respectively, exceeding WHO recommendations of < 30% and < 20%. Adherence to the Nigerian Essential Drug List was 91.01%. Conclusion Despite high knowledge and adherence to EDL, significant gaps exist in the practical application of RDP among Nigerian Navy physicians. Structured training programs, regular audits, and systemic innovations such as electronic prescribing are recommended to address these gaps and improve patient outcomes.